A concerted approach to una de gato development in Peru - Jong, W. de; Melnyk, M.; Alfaro, L.; Rosales, M.; García, M. (2000)
Uncaria tomentosa and U. guianensis appear to hold a potential to become an important export commodity and a source of income for small farmers in the tropical forest belt of the country. Both species have been important in traditional healing in many South American countries. They contain about sixty substances that are being tested widely for possible medical treatments. Uncaria tomentosa has been traded from Peru since 1994 until it reached a peak export of 726 t in 1996. Despite the general discourse on the potential of species, such as these Uncaria spp., the many stakeholders with some interest in these species do not co-ordinate their activities sufficiently to enhance sustained income for the country and the rural poor. At the national level, there has been pressure on the government to implement legislation to prohibit the sales of the raw material of these species, in order to capture larger shares of benefits for the national economy. Initially false conservation arguments were used to stop collection from the wild, as there is sufficient evidence to argue that at current harvesting levels there is no threat to the two species. Regional government agencies have promoted the production of the two species without having a clear picture of future market development, allowing the possibility that much of the future production cannot be sold. Both actions may possibly negatively affect the benefits that accrue to local collectors or producers